Peningkatan Kapasitas Badan Usaha Milik Desa dan Tantangan Pemerintah Sumalata Timur - Atuna, Raflin; Harun, Nur Istiyan (Gorontalo Journal of Public Administration Studies, 2019)
The main problem in this research is how the role of the village government in strengthening the Village Owned Enterprises in the village of Deme I, Sumalata Timur District, North Gorontalo District. The purpose of this study is the role of the village government in strengthening village-owned enterprises in Deme I village, East Sumalata District, North Gorontalo District. The research method used is a quantitative method, and the type of research is descriptive. This study uses secondary data and primary data, interview data collection techniques, observation and documentation. The informants in this study were 1 village head, 1 BPD, and 2 BUMDes employees, and 1 community leader.The results showed that the role of the village government in strengthening village-owned enterprises (BUMDES) in the field of tent rental and savings and loan services, but in its implementation the policy was still experiencing obstacles, because the government's role only gave Rp. 100,000,000 so that they have not been able to optimally increase village income through BUMDes. Factors that have hampered the development of BUMDes in Deme I Village, East Sumalata Subdistrict are the lack of maximum Capital Strength Assistance, Development of Facilities and Infrastructure, Business Network Development, Marketing and Business Partnerships, and Human Resource Development. Permasalahan pokok dalam penelitian adalah bagaimana peran pemerintah desa dalam penguatan Badan Usaha Milik Desa Di desa Deme I Kecamatan Sumalata Timur Kabupaten Gorontalo Utara. Tujuan penelitian ini peran pemerintah desa dalam penguatan Badan Usaha Milik Desa Di desa Deme I Kecamatan Sumalata Timur Kabupaten Gorontalo Utara. Metode penelitian yang digunakan adalah metode kuantitatif, dan jenis penelitian adalah deskriptif. Penelitian ini menggunakan data sekunder dan data primer, teknik pengumpulan data wawancara, observasi dan dokumentasi. Informan dalam penelitian ini adalah 1 orang Kepala Desa,1 orang BPD, dan 2 orang pegawai BUMDes, dan 1 orang tokoh masarakat.Hasil penelitian menunjukkan bahwa Peran Pemerintah desa dalam penguatan badan usaha milik desa (BUMDES) di bidang usaha jasa sewa tenda dan simpan pinjam, namun dalam implementasinya kebijakan tersebut masih mengalami kendala, karena peran pemerintah hanya memberi Rp. 100.000.000,- sehingga belum dapat secara maksimal meningkatkan pendapatan desa melalui BUMDes. Faktor-faktor yang menghambat perkembangan BUMDes di Desa Deme I Kecamatan Sumalata Timur adalah kurang maksimalnya Bantuan Penguatan Modal, Pembangunan Sarana dan Prasarana, Pengembangan Jaringan Usaha, Pemasaran dan Kemitraan Usaha, dan Pengembangan Sumber Daya Manusia.